The efficacy of non-depolarizing muscle relaxant as adjuvants to local anesthesia in peribulbar block during cataract surgery - Ainelmarwa Abdelmonem Abdallah Hassan; Fatma Alzahraa Roshdy Elkemary; Heba Mahmoud Abdelrahman (Scientific Reports)
Abstract Peribulbar anesthesia is mainly used for cataract surgery. Many studies had used atracurium and rocuronium as an additive to the local anesthetic (LA) drugs in eye surgery. The aim of this study is to evaluate the efficacy of adding atracurium versus rocuronium to a local anesthetic mixture, in providing an early onset of orbital akinesia and corneal anesthesia during cataract surgery. Ninety-three patients met the inclusion criteria and gave a written informed consent to participate. Patients were randomly allocated in three study groups (31 patients in each group). Group I received either 3 mL of a lidocaine2%(mixed by hyaluronidase 50 IU/ml) and 3 ml bupivacaine mixture, plus 0.5 mL rocuronium (5 mg) total volume 6.5 ml. Group II 3 mL of a lidocaine2%(mixed by hyaluronidase 50 IU/ml) and 3 ml bupivacaine mixture plus 0.5 mL (5 mg) atracurium total volume 6.5 ml. Group III or3 mL of a lidocaine2%(mixed by hyaluronidase 50 IU/ml) and − 3 ml bupivacaine mixture, plus 0.5 mL saline total volume 6.5 ml. The onset time of orbital akinesia was significantly lower in the rocuronium group and the atracurium group compared to the control group. Akinesia score was (0.90 ± 0.30) and (0.19 ± 0.40) in rocuronium group at 4 min and 6 min respectively which result in highly significant difference than atracurium and control groups. The use of rocuronium and atracurium will result in rapid orbital akinesia and rapid orbicularis muscle akinesia.